2012
DOI: 10.1093/hmg/dds118
|View full text |Cite
|
Sign up to set email alerts
|

Clustered burst firing in FMR1 premutation hippocampal neurons: amelioration with allopregnanolone

Abstract: Premutation CGG repeat expansions (55-200 CGG repeats; preCGG) within the fragile X mental retardation 1 (FMR1) gene cause fragile X-associated tremor/ataxia syndrome (FXTAS). Defects in neuronal morphology and migration have been described in a preCGG mouse model. Mouse preCGG hippocampal neurons (170 CGG repeats) grown in vitro develop abnormal networks of clustered burst (CB) firing, as assessed by multielectrode array recordings and clustered patterns of spontaneous Ca(2+) oscillations, neither typical of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
121
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

4
5

Authors

Journals

citations
Cited by 93 publications
(131 citation statements)
references
References 69 publications
6
121
0
1
Order By: Relevance
“…The MFR observed for the control populations was within range of published values using MEA systems (Eytan and Marom 2006;Cao et al 2012;Bateup et al 2013;Colombi et al 2013;Lignani et al 2013). We found that inhibition of miR-128 resulted in increased MFR, increased burst rate, and an increase in the number of network events in both immature and mature cultures.…”
Section: Discussionsupporting
confidence: 81%
“…The MFR observed for the control populations was within range of published values using MEA systems (Eytan and Marom 2006;Cao et al 2012;Bateup et al 2013;Colombi et al 2013;Lignani et al 2013). We found that inhibition of miR-128 resulted in increased MFR, increased burst rate, and an increase in the number of network events in both immature and mature cultures.…”
Section: Discussionsupporting
confidence: 81%
“…[45,46] Mouse models of the fragile X premutation have found reduced induction of long-term potentiation (LTP) and increases in both NMDA and mGluR-mediated LTD.[47] These effects are large 10-20 minutes post-conditioning, and then became smaller and insignificant by 40-50 minutes. [47] Hippocampal neurons from mice with the fragile X premutation show a clustered burst firing pattern and imbalanced excitatory–inhibitory (i.e., glutamate-GABA) neurotransmission [48]. Further studies with cognitive ERP/EEG and brain-imaging modalities are needed to determine the macroscopic effects of the synaptic dysfunction in both FXTAS and AD, and elucidate their impact on memory, language and other cognitive processes.…”
Section: Discussionmentioning
confidence: 99%
“…In FMR1 gene knockout mouse model, enhanced mGluR5 signaling has been demonstrated and contributes to long-term synaptic depression during synaptic transmission. Such disturbances in mGluR5 signaling are thought to elicit cognitive as well as syndromic features of fragile X syndrome (Huber et al, 2002;Bear et al, 2004;Dolen and Bear, 2008), and FMR1 premutation (Chen et al, 2010;Cao et al, 2012b;Liu et al, 2012). Our in vitro observation that nanomolar bifenthrin alters neuronal Ca 21 dynamics and mGluR5 signaling activity with consequential changes in neurite outgrowth provides evidence for a new paradigm in understanding how certain pyrethroids might influence health outcomes that involve abnormal neuronal network development associated with developmental disorders.…”
mentioning
confidence: 80%
“…The sample preparation for Western blot was performed as described previously (Cao et al, 2012b). An equal amount of sample protein (20 mg) was loaded onto the wells of 10% SDS-PAGE gels and transferred to a nitrocellulose membrane by electroblotting.…”
Section: Methodsmentioning
confidence: 99%